2019
DOI: 10.1123/jmld.2017-0046
|View full text |Cite
|
Sign up to set email alerts
|

Object Control Skills Mediate the Relationship Between Neighborhood Vulnerability and Participation in Physical Activities

Abstract: This study examined the influence of physical health and well-being vulnerability on participation in physical activities, and whether motor skill proficiency mediated this relationship. Kindergarten children (n = 260) completed the Test of Gross Motor Development-2 and the Children's Assessment of Participation and Enjoyment survey. A multivariate analysis of covariance was used to compare the motor skills and participation in physical activities of children in schools classified as more or less vulnerable. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…With regard to the sociocultural factors, when analyzing the findings referring to socioeconomic level, the students from schools with low vulnerability, i.e., a better socioeconomic level, had higher motor performances. These findings are in line with several studies [ 42 , 43 , 71 ] that point to the existence of inequality in the development of MC, where socially underprivileged children perform more poorly than socially advantaged children. The students who attend schools with low vulnerability belong to the families with greater economic resources, so they have access to more types of extracurricular physical activity programs [ 72 , 73 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to the sociocultural factors, when analyzing the findings referring to socioeconomic level, the students from schools with low vulnerability, i.e., a better socioeconomic level, had higher motor performances. These findings are in line with several studies [ 42 , 43 , 71 ] that point to the existence of inequality in the development of MC, where socially underprivileged children perform more poorly than socially advantaged children. The students who attend schools with low vulnerability belong to the families with greater economic resources, so they have access to more types of extracurricular physical activity programs [ 72 , 73 ].…”
Section: Discussionsupporting
confidence: 92%
“…In relation to sociocultural factors, the socioeconomic level seems to be relevant in the development of MC, where children from vulnerable settings present lower MC and participation in physical activity [ 42 ]; however, systematic review evidence has reported inconsistent associations [ 35 ]. Object control tasks appear to be a mediator in the link between vulnerability and physical activity, as the most vulnerable children likely have less access to equipment necessary for various object control activities [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the behavioral explanations of the health-related associations of socio-economic status, low physical activity levels seem to play an important role [130,131]. Emerging evidence indicates that children from ethnic minorities, disadvantaged and poor environments show lower levels of MC [132]. Some disparities may exist regarding the opportunities for MC development for these children [121,122], which consequently, may lead to further disparities in physical activity levels throughout the lifespan, thereby perpetuating the cycle of poverty.…”
Section: What We Knowmentioning
confidence: 99%
“…Some disparities may exist regarding the opportunities for MC development for these children [121,122], which consequently, may lead to further disparities in physical activity levels throughout the lifespan, thereby perpetuating the cycle of poverty. For example, Temple et al [132] found that object control skills mediated the relationship between neighborhood vulnerability and participation in physical activities among children in their first year of school. Concomitantly, children from more vulnerable neighborhoods began their school career with lower motor skill proficiency than children from less vulnerable neighborhoods.…”
Section: What We Knowmentioning
confidence: 99%